2021
DOI: 10.3390/land10030289
|View full text |Cite
|
Sign up to set email alerts
|

GHG Balance of Agricultural Intensification & Bioenergy Production in the Orinoquia Region, Colombia

Abstract: Energy crop expansion can increase land demand and generate displacement of food crops, which impacts greenhouse gas (GHG) emissions mainly through land-use change (LUC). Increased agricultural productivity could compensate for this. Our study aims to evaluate the regional combined GHG emissions of increasing agricultural yields for food crop and beef production and using the generated surplus land for biomass production to replace fossil fuels in the Orinoquia region of Colombia until 2030. The results show t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…The results of the mitigation potential analysis reported in Ali et al [ 70 ] provides evidence that the adoption of low-emission energy technologies can significantly reduce GHG emissions in developing countries to help meet the 2050 goals. Ramírez-Contreras [ 71 ] found that renewable energy in the form of bioenergy has the potential to reduce fossil fuel dependence in the Orinoquia region of Colombia by 2030, offering the opportunity to slow down the rate of GHG emissions in this region. Moreover, using proper technology platforms (e.g., geospatial technology, and precision agriculture) with perennial bioenergy crops can not only increase feedstock supply for renewable biofuel production but also improve soil health, sequester carbon, and provide habitat for pollinators and other wildlife species [ 66 , 72 , 73 ].…”
Section: Resultsmentioning
confidence: 99%
“…The results of the mitigation potential analysis reported in Ali et al [ 70 ] provides evidence that the adoption of low-emission energy technologies can significantly reduce GHG emissions in developing countries to help meet the 2050 goals. Ramírez-Contreras [ 71 ] found that renewable energy in the form of bioenergy has the potential to reduce fossil fuel dependence in the Orinoquia region of Colombia by 2030, offering the opportunity to slow down the rate of GHG emissions in this region. Moreover, using proper technology platforms (e.g., geospatial technology, and precision agriculture) with perennial bioenergy crops can not only increase feedstock supply for renewable biofuel production but also improve soil health, sequester carbon, and provide habitat for pollinators and other wildlife species [ 66 , 72 , 73 ].…”
Section: Resultsmentioning
confidence: 99%
“…LCI for the production of RS was obtained for Colombia conditions, in the Orinoquia region [2] . RS production encompasses both cultivation and harvest stages.…”
Section: Life Cycle Inventorymentioning
confidence: 99%
“…Paddy rice and RS were considered as main outputs. Diesel, land, and fertilizer requirements for rice production was obtained from the literature review [2] . Emissions of the agricultural stage was determined according to the IPCC methodology.…”
Section: Life Cycle Inventorymentioning
confidence: 99%
“…There are many examples showing how the agriculture and forestry sectors can devise management approaches that enable biomass production and use for energy in conjunction with supply of food, construction timber and other bio‐based products, while avoiding further conversion of natural ecosystems. Principal means include changes in agriculture practices to increase cropping intensities and yields and improve livestock productivity (Andrade et al, 2017; Brinkman et al, 2021; Cassman & Grassini, 2020; de Souza et al, 2019; Gerssen‐Gondelach et al, 2017; Ramírez‐Contreras et al, 2021), forest management practices enabling biomass harvest for energy (Dale et al, 2017; Ghaffariyan et al, 2017; Spinelli, 2019), and changes to industrial processes to improve biomass conversion efficiencies and use residues and waste to meet internal process energy needs and produce fuels, electricity and heat for use outside the industry (Hagman et al, 2018; Isaksson et al, 2012; Negri et al, 2020; Pettersson & Harvey, 2012). Furthermore, new biomass production systems can be integrated with existing agriculture and forestry systems (incl.…”
Section: The Potential Co‐benefits and Adverse Side Effects Of Bioenergy Systemsmentioning
confidence: 99%